A STUDY OF RISK FACTORS AFFECTING CONSTRUCTION PROJECT EXECUTION IN THE CENTRAL REGION OF GHANA. - Bentum Mensah, Frank; Tsotorvor, Godfred; K.Tsorgali, Engr.Michael; Kodwo Fordjour, Francis (International Journal of Scientific Research and Management (IJSRM), 2023)
The construction industry is one of the most dynamic, risky, and challenging businesses.  The number of risks present invariably goes beyond those found in other industries. The research was conducted with the aim of exploring the various risk factors affecting late execution of construction projects in the Central region of Ghana. Purposive sampling technique was used to select thirty (30) contractors of on-going projects for the study. Questionnaire was used to illicit information from the participants. Findings of the research revealed that financial, economic as well as political risk are the major factors contributing to late execution of construction projects in the central region of Ghana.The conclusion drawn from the research indicated a lot of projects have not been completed. A thorough feasibility studies should be undertaken before any project is done.